Study of the γ-U(Mo) phase decomposition for atomised and ground powders. (August 2015) - Champion, G.; Iltis, X.; Tougait, O.; Pasturel, M.; Belin, R.; Palancher, H.; Richaud, J.-C.
Abstract: U(Mo) particles are obtained by centrifugal atomisation or by mechanical grinding fabrication processes and display microstructures which strongly influence the gas retention efficiency and consequently the behaviour of the fuel. Moreover, during fuel plate fabrication, a partial decomposition of the γ-U(Mo) phase toward the α-U and U2 Mo phases can occur and is supposed to influence also the irradiation behaviour of the fuel. In situ X-ray and neutron diffraction experiments have been performed in order to study the γ-U(Mo) phase decomposition for two types of powders produced by the atomisation and the grinding routes. The present study allows assessing differences between these powders, in terms of γ-U(Mo) phase decomposition kinetics and mechanisms. Highlights: In-situ diffraction studies have been performed on the two reference U(Mo) powders. γ-U(Mo) phase decomposition have been observed and quantified (kinetics study). Mechanisms of decomposition in link with the [Mo] content variations have been described.